Risk factors for multidrug‐resistant organisms among deceased organ donors. Issue 9 (26th June 2019) - Anesi, Judith A.; Blumberg, Emily A.; Han, Jennifer H.; Lee, Dong H.; Clauss, Heather; Climaco, Antonette; Hasz, Richard; Molnar, Esther; Alimenti, Darcy; West, Sharon; Bilker, Warren B.; Tolomeo, Pam; et al.
Abstract : Donor infection or colonization with a multidrug‐resistant organism (MDRO) affects organ utilization and recipient antibiotic management. Approaches to identifying donors at risk of carrying MDROs are unknown. We sought to determine the risk factors for MDROs among transplant donors. A multicenter retrospective cohort study was conducted at four transplant centers between 2015 and 2016. All deceased donors who donated at least one organ were included. Cultures obtained during the donor's terminal hospitalization and organ procurement were evaluated. The primary outcome was isolation of an MDRO on culture. Multivariable Cox regression was used to determine risk factors associated with time to donor MDRO. Of 440 total donors, 64 (15%) donors grew an MDRO on culture. Predictors of an MDRO on donor culture included hepatitis C viremia (hazard ratio [HR] 4.09, 95% confidence interval [CI] 1.71‐9.78, P  =   .002), need for dialysis (HR 4.59, 95% CI 1.09‐19.21, P  =   .037), prior hematopoietic cell transplant (HR 7.57, 95% CI 1.03‐55.75, P  =   .047), and exposure to antibiotics with a narrow gram‐negative spectrum (HR 1.13, 95% CI 1.00‐1.27, P  =   .045). This is the first study to determine risk factors for MDROs among deceased donors and will be important for risk stratifying potential donors and informing transplant recipient prophylaxis. Abstract : Anesi and colleagues determine risk factors for multidrug‐resistant bacterial organisms among deceased organ donors, including donor hepatitis C infection, renal replacement therapy, prior hematopoietic cell transplant, and exposure to antibiotics with a narrow gram‐negative spectrum during their terminal hospitalization. See Kaul's editorial on page 2403 .